The Heaviside cover-up method, named after Oliver Heaviside, is a technique for quickly determining the coefficients when performing the partial-fraction expansion of a rational function in the case of linear factors.[1] [2] [3] [4]
Separation of a fractional algebraic expression into partial fractions is the reverse of the process of combining fractions by converting each fraction to the lowest common denominator (LCD) and adding the numerators. This separation can be accomplished by the Heaviside cover-up method, another method for determining the coefficients of a partial fraction. Case one has fractional expressions where factors in the denominator are unique. Case two has fractional expressions where some factors may repeat as powers of a binomial.
In integral calculus we would want to write a fractional algebraic expression as the sum of its partial fractions in order to take the integral of each simple fraction separately. Once the original denominator, D0, has been factored we set up a fraction for each factor in the denominator. We may use a subscripted D to represent the denominator of the respective partial fractions which are the factors in D0. Letters A, B, C, D, E, and so on will represent the numerators of the respective partial fractions. When a partial fraction term has a single (i.e. unrepeated) binomial in the denominator, the numerator is a residue of the function defined by the input fraction.
We calculate each respective numerator by (1) taking the root of the denominator (i.e. the value of x that makes the denominator zero) and (2) then substituting this root into the original expression but ignoring the corresponding factor in the denominator. Each root for the variable is the value which would give an undefined value to the expression since we do not divide by zero.
General formula for a cubic denominator with three distinct roots:
\ellx2+mx+n | |
(x-a)(x-b)(x-c) |
=
A | |
(x-a) |
+
B | |
(x-b) |
+
C | |
(x-c) |
Where
A=
\ella2+ma+n | |
(a-b)(a-c) |
;
and where
B=
\ellb2+mb+n | |
(b-c)(b-a) |
;
and where
C=
\ellc2+mc+n | |
(c-a)(c-b) |
.
Factorize the expression in the denominator. Set up a partial fraction for each factor in the denominator. Apply the cover-up rule to solve for the new numerator of each partial fraction.
3x2+12x+11 | |
(x+1)(x+2)(x+3) |
=
A | |
x+1 |
+
B | |
x+2 |
+
C | |
x+3 |
Set up a partial fraction for each factor in the denominator. With this framework we apply the cover-up rule to solve for A, B, and C.
Proceed similarly for B and C.
D2 is x + 2; For the residue B use x = -2.
D3 is x + 3; For residue C use x = -3.
Thus, to solve for A, use x = -1 in the expression but without D1:
3x2+12x+11 | |
(x+2)(x+3) |
=
3-12+11 | |
(1)(2) |
=
2 | |
2 |
=1=A.
Thus, to solve for B, use x = -2 in the expression but without D2:
3x2+12x+11 | |
(x+1)(x+3) |
=
12-24+11 | |
(-1)(1) |
=
-1 | |
(-1) |
=+1=B.
Thus, to solve for C, use x = -3 in the expression but without D3:
3x2+12x+11 | |
(x+1)(x+2) |
=
27-36+11 | |
(-2)(-1) |
=
2 | |
(+2) |
=+1=C.
Thus,
3x2+12x+11 | |
(x+1)(x+2)(x+3) |
=
1 | |
x+1 |
+
1 | |
x+2 |
+
1 | |
x+3 |
When factors of the denominator include powers of one expression we
From the equation of numerators we solve for each numerator, A, B, C, D, and so on.This equation of the numerators is an absolute identity, true for all values of x. So, we may select any value of x and solve for the numerator.
3x+5 | |
(1-2x)2 |
=
A | |
(1-2x)2 |
+
B | |
1-2x |
Here, we set up a partial fraction for each descending power of the denominator. Then we solve for the numerators, A and B. As
(1-2x)
(1-2x)
3x+5=A+B(1-2x)
n
n
Ak
(1-2x)k
k
n
An
A1
n=2
A=A2
B=A1
To solve for
A
A
1-2x=0
Solving for
x
A
x=1/2
When we substitute this value,
x=1/2
3\left( | 1 |
2 |
\right)+5=A+B(0)
A= | 3 | +5= |
2 |
13 | |
2 |
To solve for
B
Since the equation of the numerators, here,
3x+5=A+B(1-2x)
x
x
B
As we have solved for the value of
A
A=13/2
B
We may pick
x=0
A=13/2
B
\begin{align} 3x+5&=A+B(1-2x)\\ 0+5&=
13 | |
2 |
+B(1+0)\\
10 | |
2 |
&=
13 | |
2 |
+B\\ -
3 | |
2 |
&=B\\ \end{align}
We may pick
x=1
B
\begin{align} 3x+5&=A+B(1-2x)\\ 3+5&=
13 | |
2 |
+B(1-2)\\ 8&=
13 | |
2 |
+B(-1)\\
16 | |
2 |
&=
13 | |
2 |
-B\\ B&=-
3 | |
2 |
\end{align}
We may pick
x=-1
B
\begin{align} 3x+5&=A+B(1-2x)\\ -3+5&=
13 | |
2 |
+B(1+2)\\
4 | |
2 |
&=
13 | |
2 |
+3B\\ -
9 | |
2 |
&=3B\\ -
3 | |
2 |
&=B \end{align}
Hence,
3x+5 | |
(1-2x)2 |
=
13/2 | |
(1-2x)2 |
+
-3/2 | |
(1-2x) |
,
or
3x+5 | |
(1-2x)2 |
=
13 | |
2(1-2x)2 |
-
3 | |
2(1-2x) |